Crystalline Lattice‐Confined Atomic Pt in Metal Carbides to Match Electronic Structures and Hydrogen Evolution Behaviors of Platinum - Ma, Tian; Cao, Hao; Li, Shuang; Cao, Sujiao; Zhao, Zhenyang; Wu, Zihe; Yan, Rui; Yang, Chengdong; Wang, Yi; Aken, Peter A.; Qiu, Li; Wang, Yang‐Gang; et al. (Advanced materials (Weinheim), 2022)
Platinum‐based catalysts occupy a pivotal position in diverse catalytic applications in hydrogen chemistry and electrochemistry, for instance, the hydrogen evolution reactions (HER). While adsorbed Pt atoms on supports often cause severe mismatching on electronic structures and HER behaviors from metallic Pt due to the different energy level distribution of electron orbitals. Here, the design of crystalline lattice‐confined atomic Pt in metal carbides using the Pt‐centered polyoxometalate frameworks with strong PtO‐metal covalent bonds is reported. Remarkably, the lattice‐confined atomic Pt in the tungsten carbides (Ptdoped@WCx, both Pt and W have atomic radii of 1.3 Å) exhibit near‐zero valence states and similar electronic structures as metallic Pt, thus delivering matched energy level distributions of the Pt 5dz2 and H 1s orbitals and similar acidic hydrogen evolution behaviors. In alkaline conditions, the Ptdoped@WCx exhibits 40 times greater mass activity (49.5 A mgPt−1 at η = 150 mV) than the Pt@C because of the favorable water dissociation and H* transport. These findings offer a universal pathway to construct urgently needed atomic‐scale catalysts for broad catalytic reactions. Crystalline lattice‐confined atomic Pt in metal carbides with “real” matched properties as metallic platinum are developed using Pt‐centered polyoxometalate frameworks with strong PtOW/Mo covalent bonds. The WC lattice‐confined Pt atoms exhibit near‐zero valence states, similar electronic structures, and matched hydrogen evolution behaviors as Pt(111) surface; remarkably, they offer 40 times greater mass activity than Pt@C‐20% in alkaline conditions.